Mechanical properties analysison FSW butt joint of aluminum alloy that applied in marine industries - Rahadian Nopriantoko (Politeknik Negeri Lhokseumawe, 2022)
Friction Stir Welding (FSW) was promoted as a new welding method, cheap and eco-friendly welding with good quality joints. Aluminum Alloy is used widely in industries, including the marine industry. AA 5XXX and 6XXX series are materials used for shipping manufacture and offshore construction, because of their corrosive resistance and good strength properties after joining. Similar butt joint welding using the FSW method for a number of aluminum alloy series AA 5052, AA 5083, AA 6061, AA 6063. Welding samples were made using AWS standards and then given radiographic testing to determine the general condition of the welds. Then a tensile strength test was carried out using a ZwickRoell tensile testing machine and a hardness test using a microhardness Vickers Buehler with ASTM standards on the welding results to analyze the mechanical properties of the welded joint zone, as well as compare each result and get the ratio of the number of mechanical properties of the joint results the weld to the base material. After that, the results and discussion were obtained that the weld area showed different mechanical properties for each series of aluminum alloys. The value of the tensile strength, when compared to the tensile strength of the base metal, is around 60-75%, while the hardness value is around 75-80.6 HV for all the welded samples.